Analysis of dermoscopic characteristic for the differential diagnosis of palmoplantar psoriasis and palmoplantar eczema. Issue 5 (5th February 2021) - Yu, Xiaoping; Wei, Guo; Shao, Chunchun; Zhu, Mingjie; Sun, Shuna; Zhang, Xiaojie
Abstract : Abstract: Dermoscopy is a noninvasive diagnostic technique that is of great value for the differential diagnosis of palmoplantar psoriasis and palmoplantar eczema. Considering the particularity of palmoplantar anatomy, the dermoscopic features of psoriasis and eczema in palm region show fewer differences, compared with those in other parts of the body. Only a few studies have examined the palmoplantar region of psoriasis and eczema patients under a dermoscope. A total of 26 patients with palmoplantar psoriasis and 31 patients with palmoplantar eczema were enrolled in our study. Target palmoplantar areas were observed through general observation and under dermoscope. We found that the presence of white scales and a regular arrangement of dots and globular vessels were significantly indicative of palmoplantar psoriasis, while yellowish scales and an irregular arrangement of atypical vessels were significantly indicative of palmoplantar eczema.